Thru-Hole Epitaxy: A Highway for Controllable and Transferable Epitaxial Growth - Jang, Dongsoo; Ahn, Chulwoo; Lee, Youngjun; Lee, Seungjun; Lee, Hyunkyu; Kim, Donghoi; Kim, Yongsun; Park, Ji Yong; Kwon, Young Kyun; Choi, Jaewu; Kim, Chinkyo (Advanced Materials Interfaces, 2023)
Controllable growth and facile transferability of a crystalline film with desired characteristics, acquired by tuning composition and crystallographic orientation, become highly demanded for advanced flexible devices. Here the desired crystallographic orientations and facile transferability of a crystalline film can be achieved by “thru-hole epitaxy” in a straightforward and undemanding manner with no limitation on the layer number and polarity of a 2D space layer and the surface characteristics. The crystallographic alignment can be established by the connectedness of the grown material to the substrate through a small net cross-sectional area of thru-holes, which also allows the straightforward detachment of the grown material. Thru-hole epitaxy can be adopted for the realization of advanced flexible devices on large scale with desired crystallographic orientation and facile transferability.
Keywords: Controllable growth; Crystalline films; Crystallographic alignment; Crystallographic orientations; Density-functional-theory; Flexible device; Hexagonal boron nitride; Layer number; Thru-hole epitaxy; Transferability; crystallographic alignment; density functional theory; gallium nitride; hexagonal boron nitride; thru-hole epitaxy; transferability